Solution focused brief therapy(SFBT): strategies to reduce cyberbullying behavior student - Dalimunthe, Lenni; Daulay, Nurussakinah; Manurung, Purbatua (Universitas Islam Negeri Raden Intan Lampung, 2023)
The problem in this study is the high behaviour of cyberbullying among adolescents. This research focuses on group counselling with the Solution Focused Brief Therapy (SFBT) approach which aims to reduce cyberbullying behaviour in friends by helping them calm down to achieve their educational goals. This study uses a quantitative research design with quasi-experiments. To collect respondents used a purposive sampling method to obtain 30 students from all students of class XI. The instrument used in this study is the cyberbullying scale. The results of the study show that it is concluded that Solution Focused Brief Therapy (SFBT) can reduce cyberbullying behaviour, the approach used uses a more positive perspective on the counselee so that the counselee is treated as a